Politeness in Korean Sign Language from a cross-linguistic perspective - 이정아; 김현아; 최영주 (Linguistic research, 2024)
Previous research has shown that sign languages share socio-cultural norms, such as 'politeness,' with spoken/written languages. For example, in Japanese Sign Language (JSL), a head nod and bending the upper body are exclusively observed in polite signing contexts, demonstrating that JSL shares politeness norms with Japanese (Yoon and Kim 2022). Similar to Japanese, Korean has a well-defined honorification to convey politeness (e.g., Brown et al. 2014), and we therefore assume that Korean Sign Language (KSL) may also have systematic strategies to mark politeness. We recruited a native KSL signer and sign language interpreter to compare nonmanual features between two different hierarchical orders (a superior versus a peer/subordinate), and across different contexts (apology vs. compliment). Our findings reveal that, similar to JSL, KSL shows nonmanual characteristics, such as squinted eyes, head nods, narrowed shoulders, and upper body bending, in polite settings. We interpret upper body bending as a feature that likely reflects language contact with spoken/written Korean, embodying Korean politeness culture. Moreover, our results suggest that a smaller signing space may not always indicate more politeness. Unlike previous findings, our study shows that a larger signing space is employed to mark more politeness in emphasizing lexical signs. Our study primarily attempts to investigate systematic relationships between nonmanual features, contexts, hierarchical orders, and politeness. KCI Citation Count: 0